Diversity and functionality of plasmid-borne VagCD toxin–antitoxin systems of Klebsiella pneumoniae. (23rd January 2017) - Duprilot, Marion; Decre, Dominique; Genel, Nathalie; Drieux, Laurence; Sougakoff, Wladimir; Arlet, Guillaume
Abstract : Objectives: To explore the VagCD toxin–antitoxin (TA) systems encoded on plasmids in multiresistant Klebsiella pneumoniae strains. Methods: Previously sequenced K. pneumoniae plasmids were used for in silico analysis and a collection of 63 resistant K. pneumoniae strains was used for epidemiological study. Functional analysis was done after separate cloning of the toxin gene under the control of the arabinose-inducible promoter of pBAD43 and of the antitoxin gene under the control of the constitutive promoter of pUC19. Results: In silico, two types of VagCD systems, VagCD1 and VagCD2, encoded on K. pneumoniae plasmids could be distinguished, 15% carrying one of these TA systems. Moreover, in a collection of antibiotic-resistant K. pneumoniae strains including ESBL or carbapenemase producers, 17.5% of isolates were found to harbour a VagCD TA system. VagCD1 and VagCD2 were proved functional TA systems, with VagD the toxin and VagC its antitoxin, not only in K. pneumoniae but also in Escherichia coli and other Enterobacteriaceae. Toxin expression was found to induce a significant decrease in a bacterial population resulting from both bactericidal and bacteriostatic effects. Conclusions: The vagCD genes of K. pneumoniae encode a functional broad-spectrum TA system and are conserved on the large multiple antibiotic resistance-conferring plasmids in this species.